2020
DOI: 10.1248/bpb.b20-00442
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Antioxidant Stress-Responsive Transcription Factor Nrf2 Target Gene in the Reduction of Radiation Damage by the Thrombocytopenia Drug Romiplostim

Abstract: Ionizing radiation induces severe oxidative stress, resulting in individual death by acute radiation syndrome. The nuclear factor-erythroid-2-related factor 2 (Nrf2) plays an important role in the antioxidant response pathway. Recently, romiplostim (RP), an idiopathic thrombocytopenic purpura therapeutic drug, was reported to completely rescue mice exposed to lethal total-body irradiation (TBI). However, the details underlying the mechanism for reducing radiation damage remain largely unknown. To elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Our previous studies showed that the RP completely rescued mice exposed to lethal total-body irradiation (TBI), suggesting that RP may not only promote hematopoiesis in various organs in irradiated individuals but also mitigate the dysfunction or regenerate the original function in multiple organs [13]. Previous studies have reported the following mechanisms by which RP exerts its radiation-mitigating effects on individuals exposed to radiation: restoration of the cell count in hematopoietic tissues, such as bone marrow and spleen; enhancement of DNA double-strand break repair and inhibition of apoptosis in hematopoietic cells [13]; and regulation of the expression of defense genes by the Nrf2-Keap1 system to regulate the expression of defense genes [14]. Although the function of RP in acute radiation injury is clear, the detailed mechanisms underlying how RP rescues mice exposed to lethal doses of radiation are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the RP completely rescued mice exposed to lethal total-body irradiation (TBI), suggesting that RP may not only promote hematopoiesis in various organs in irradiated individuals but also mitigate the dysfunction or regenerate the original function in multiple organs [13]. Previous studies have reported the following mechanisms by which RP exerts its radiation-mitigating effects on individuals exposed to radiation: restoration of the cell count in hematopoietic tissues, such as bone marrow and spleen; enhancement of DNA double-strand break repair and inhibition of apoptosis in hematopoietic cells [13]; and regulation of the expression of defense genes by the Nrf2-Keap1 system to regulate the expression of defense genes [14]. Although the function of RP in acute radiation injury is clear, the detailed mechanisms underlying how RP rescues mice exposed to lethal doses of radiation are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These two enzymes share many similarities with GPX4, such as their use of glutathione as a cofactor, their peroxidase activity toward lipids, and their ability to inhibit ferroptosis. Previous studies indicate that knockdown of intracellular Prdx6 in multiple tumor cell lines enhances lipid peroxidation and erastin- or RSL3-induced ferroptosis ( 23 , 26 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The thrombopoietin receptor agonist RP (Romiplate ® , Kyowa Kirin, Tokyo, Japan), as an ARS mitigator, was intraperitoneally administered once daily for 3 consecutive days to irradiated mice, starting immediately after TBI (within 2 h, 24 h, and 48 h post-TBI). The applied dose of RP was 50 µg/kg of body weight/day prepared with Normal Saline Solution (NSS; Otsuka Pharmaceutical, Tokyo, Japan) as the vehicle [13][14][15][16][17][18]. In addition to mice that received both TBI and RP (TBI + RP group), mice treated with TBI and NSS (TBI + NSS group), mice treated with RP only (0 Gy + RP group), and those treated with NSS only (0 Gy + NSS group) were prepared in this study.…”
Section: Administration Of Ars Protective/mitigative Agentsmentioning
confidence: 99%
“…The thrombopoietin receptor agonist RP was recently approved by the FDA to improve survival in patients acutely exposed to myelosuppressive doses of radiation [11][12][13][14][15][16][17][18]. To confirm the radio-mitigative and life-saving effects of RP in our mouse model of severe ARS caused by lethal TBI, we monitored the changes in body weight and the level of animal survival over a period of 30 days (Figure 1A).…”
Section: Evs Collected From Mice That Overcame Ars With Rp Treatment ...mentioning
confidence: 99%
See 1 more Smart Citation